2007
DOI: 10.1002/14651858.cd003190.pub4
|View full text |Cite
|
Sign up to set email alerts
|

Anticholinergic drugs versus other medications for overactive bladder syndrome in adults

Abstract: BackgroundOveractive bladder syndrome is defined as "urgency with or without urge incontinence, usually with frequency and nocturia". It is a common condition with significant economic and quality of life implications. While the condition's pathophysiology remains to be fully elucidated, pharmacotherapy is the main treatment option. Despite uncertainty as to drug treatment of choice, anticholinergics are increasingly being used in primary and secondary care settings. This review compares anticholinergic drugs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 45 publications
0
30
0
5
Order By: Relevance
“…There is no evidence to suggest flavoxate should be used in treatment of overactive bladder. 5 6. Others: Includes calcium channel blockers like verapamil, potassium channel openers like pinacidil and cromakalim and Gamma-aminobutyric acid GABA agonists like baclofen.…”
Section: Overactive Bladdermentioning
confidence: 99%
See 1 more Smart Citation
“…There is no evidence to suggest flavoxate should be used in treatment of overactive bladder. 5 6. Others: Includes calcium channel blockers like verapamil, potassium channel openers like pinacidil and cromakalim and Gamma-aminobutyric acid GABA agonists like baclofen.…”
Section: Overactive Bladdermentioning
confidence: 99%
“…There were no demonstrable improvements in urodynamic parameters with verapamil. 5 1. Intravesical botulinum toxin 6 appears to be an effective therapy for refractory OAB symptoms, but as yet little data exist on benefits and safety compared with other interventions, or with placebo.…”
Section: What Is the Place Of Anticholinergic Drugs?mentioning
confidence: 99%
“…Reported adverse events included dry mouth, dizziness, nausea, blurred vision, swelling of lips, diarrhea and constipation. Of 142 patients receiving flavoxate, 22 experienced adverse effects, and of 122 receiving anticholinergic treatment, 50 experienced adverse effects (RR 2.28, 95 % CI 1.45 to 3.56) [36].…”
Section: Tolerability and Side Effectsmentioning
confidence: 99%
“…Ten studies comparing flavoxate with anticholinergics were included in a Cochrane review comparing anticholinergic drugs with other types or classes of drugs for treating OAB symptoms [36]. The review showed that there is no difference in cure rates between anticholinergic drugs and flavoxate, but adverse effects are more frequent with anticholinergic drugs than with flavoxate.…”
Section: Recent Recommendations Of Systematic Reviews and Guidelinesmentioning
confidence: 99%
See 1 more Smart Citation